The Learning Process in The Classroom Through the Mind Mapping Approach from The Philosophy of Progressivism - Jonathan Fredrik; Bagus Ardi Wibowo (Journal of Mathematics and Mathematics Education, 2019)
Education plays a role in human life to prevent people from poverty, underdevelopment, and ignorance so that it is necessary to change the way of thinking of humans themselves to overcome these problems. The progress of the human mindset is a form of change and cannot be separated from the achievement of creativity. This article aims to describe and explain the use of mind maps in mathematics learning from a progressivism point of view through the learning process carried out from the primary and secondary education levels to produce creative products that can help students improve learning achievement through the role of the teacher as a facilitator and students as a learning center. This article uses literature study method, data is collected and analyzed as secondary data including books, journals and proceedings relevant to the topic. The results showed that the mind map method could be used by teachers and students to change the concept of thinking through active student involvement through the making of mathematics learning materials, addition and building space and the area of a circle in an attractive graphic form. Progressivism views that progress in thinking is a process of change and through the mindmaping learning method the concept of subject matter can be visualized in the form of a graphic infrastructure that can stimulate the right and left brains so that it can be useful to free students from the snare of rules when starting to learn. The conclusion of this study is a change in mindset that is in line with the viewpoint of progressivism philosophy is through a mind map learning model that can produce student creativity products and the role of the teacher as a facilitator can occur.